2019
DOI: 10.1007/s12257-019-0059-9
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Toxins: From Their Pathogenic Roles to Anti-virulence Therapy Using Natural Products

Abstract: Staphylococcus aureus (S. aureus) produces a wide variety of toxins that cause various diseases in humans. S. aureus toxins are divided into three categories; (i) superantigens (SAgs) that interfere with receptor function and cause toxic shock syndrome (TSS) or staphylococcal food poisoning (SFP), (ii) exfoliative toxins (ETs) that destroy epidermal barrier functions and cause staphylococcal scalded skin syndrome (SSSS), and (iii) cytotoxins that cause cell lysis. Recently, anti-toxin neutralizing agents have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 120 publications
(195 reference statements)
1
11
0
Order By: Relevance
“…The luk-F/S-PV gene is detected more often in SSTI isolates than in SAB isolates [ 15 , 26 , 32 , 45 , 46 , 47 , 48 ], which confirms our results. The incidence of luk-F/S-PV gene in this study, however, was not high (3.0%), unlike the results of other researchers, in which it reached about 80% [ 35 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The luk-F/S-PV gene is detected more often in SSTI isolates than in SAB isolates [ 15 , 26 , 32 , 45 , 46 , 47 , 48 ], which confirms our results. The incidence of luk-F/S-PV gene in this study, however, was not high (3.0%), unlike the results of other researchers, in which it reached about 80% [ 35 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…Because many virulence factors are targets for the immune system, their downregulation or loss of agr-qs prevents further recruitment of phagocytes so is crucial for bacterial survival and long-term persistence in host cells/tissue. Strains isolated from chronic infections may also rewire their metabolism to promote biofilm production or may survive in a metabolically inactive state forming small-colony variants [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural product-based compounds that present anti-toxin properties correspond to a promising therapeutical approach to treat S. aureus infections [18]. A modified cyclodextrin compound, named IB201, is used to treat pneumonia.…”
Section: Natural Compoundsmentioning
confidence: 99%
“…However, these studies have not yet generated promising results due to toxicity and/or low bioavailability. New options are now under study with a focus on biological molecules or compounds to interfere with toxins or toxin-regulator genes, constituting a new generation of promising antistaphylococcal treatments [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Toxins of this bacterium play an important role in its pathogenesis. Recent studies, for instance, have shown an association between PVL (Panton Valentine Leukocidin) and methicillin-resistant strains of S. aureus, or the toxic shock syndrome toxin-1 gene produces a protein that causes systemic disease (Hennekinne et al 2012;Oliveira et al 2018;Kim 2019). The Exfoliative toxin is another important toxin of this bacterium that can cause complications such as staphylococcal scaly skin syndrome.…”
Section: Introductionmentioning
confidence: 99%